Implementing Student-Centered Learning Through Focus Group Discussion: A Strategic Approach to Educational Management in Al-Qur’an and Hadith Instruction - Rahmatullah; M. Suparta; Ainurrafiq (Al-Qalam Institue, 2025)
This study analyzes the implementation of the Student-Centered Learning (SCL) approach through the Focus Group Discussion (FGD) method in Qur’an–Hadith education. The research is motivated by challenges such as low student motivation, limited engagement, and the dominance of teacher-centered instruction in Islamic learning contexts. Employing a descriptive qualitative approach with a phenomenological design, data were collected through observation, interviews, and documentation. The findings reveal that the integration of SCL and FGD enhances students’ active participation, fosters critical and collaborative thinking, and deepens contextual understanding of Qur’anic and Hadith values. Teachers shift from authoritative transmitters to facilitators of learning, while students become autonomous agents who construct meaning through dialogue. From an educational management perspective, this approach encourages more participatory classroom governance, strengthens instructional leadership, and supports continuous professional development for teachers. The study concludes that the SCL–FGD model represents an effective pedagogical and managerial innovation for Islamic education—promoting interactive, reflective, and contextually relevant learning aligned with 21st-century educational goals.